Medical and social aspects of floods and their medical risk management - Vasile DUMITRAS (Asociatia de Biosiguranta si Biosecuritate, 2020)
Introduction. Currently, there is a steadily increasing trend in losses due to flooding. Nevertheless, global warming, followed by an inevitable overuse of river valleys might further contribute to an increase in the frequency and destructive power of floods. It is quite important to trace the cause and effect chain of the economic, social and ecological impacts during the flood hazard.